2016
DOI: 10.1021/jacs.6b01078
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxymethylation beyond Carbonylation: Enantioselective Iridium-Catalyzed Reductive Coupling of Formaldehyde with Allylic Acetates via Enantiotopic π-Facial Discrimination

Abstract: Chiral iridium complexes modified by SEGPHOS catalyze the 2-propanol mediated reductive coupling of branched allylic acetates 1a–1o with formaldehyde to form primary homoallylic alcohols 2a–2o with excellent control of regio- and enantioselectivity. These processes, which rely on enantiotopic π-facial discrimination of σ-allyliridium intermediates, represent the first examples of enantioselective formaldehyde C-C coupling beyond aldol addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…Furthermore, enantiotopic π-facial discrimination for the reactive allyliridium isomer is efficient, resulting in high levels of enantioselectivity. 8 Thus, by inverting the canonical behavior of methanol in its reaction with unsaturates (etherification), enantioselective C–H functionalization of methanol is achieved for the first time (Scheme 1). …”
mentioning
confidence: 99%
“…Furthermore, enantiotopic π-facial discrimination for the reactive allyliridium isomer is efficient, resulting in high levels of enantioselectivity. 8 Thus, by inverting the canonical behavior of methanol in its reaction with unsaturates (etherification), enantioselective C–H functionalization of methanol is achieved for the first time (Scheme 1). …”
mentioning
confidence: 99%
“…86 More recently, it has been shown that SEGPHOSmodified chiral iridium complex 131 can catalyze regioand enantioselective reductive coupling of allylic acetates 129 with formaldehyde to form primary homoallylic alcohols 130 using 2-propanol as a reductant (Scheme 25). 87 Iridium-catalyzed allylation of aldehyde or alcohol proelectrophiles with allene gas as the pronucleophile has also been reported (Scheme 26). 88 An inversion of enantioselectivity is observed for allene versus allyl acetate pronucleophiles using the same catalyst and ligand combination.…”
Section: Allenesmentioning
confidence: 99%
“…As well known, the hydroxymethylation is an important reaction for introduction of a hydroxymethyl group into a molecular. [15][16][17][18][19][20][21][22] It has been reported that BAs could be synthesized via hydroxymethylation of aryl halides and triflates [23] ; however, the catalyst was rather complicated and high loadings (the combination of 5 mol % Pd (dba) 2 , 12 mol% Ru-phos, and 1.5 equiv. Na 2 CO 3 ), and the reactants were expensive resulting in a high-cost route.…”
Section: Introductionmentioning
confidence: 99%